GAMBARAN PENGETAHUAN, SIKAP, DAN PERILAKU MENGENAI HIV/AIDS PADA SOPIR PARIWISATA DI DENPASAR - Ni Komang Dewi Trisia Pratiwi; I Made Suindrayasa; I Gusti Ayu Pramitaresthi (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2021)
The tourism drivers are categorized to be one of the groups which is at risk of HIV/AIDS infection. HIV/AIDS has a bad prognosis and can cause death. Therefore, the prevention of HIV/AIDS spread is needed. The importance of having knowledge about HIV/AIDS and being able to behave properly is a preventive effort that can be done by tourism drivers from the infection risk of HIV/AIDS. The aims of this study is describing the knowledge, attitude, and behavior related to HIV/AIDS of the tourism drivers in Denpasar. This study uses a descriptive method and a purposive sampling technique with the number of sample is 106 people. The result of the study shows that the majority of the male tourism drivers are 101 people; the average age is 38 years old; their last education is senior high school (71.7%) in majority, the 86 of them are married; moreover, they have worked on average for 11 years. The majority of the tourism drivers are categorized have good knowledge of the HIV/AIDS (51.9%). There are 56 drivers who have a positive attitude towards the HIV/AIDS (52.8%). Furthermore, there are 42.5% of the tourism drivers who own risky behavior for the HIV/AIDS infection. Based on this result, the other researchers are expected to conduct further studies related to the factors which influence the behavior which is at risk for the HIV/AIDS affection owned by the tourism drivers in Denpasar; moreover, the health institute is expected to conduct the HIV/AIDS checks for them.